Assessrnent of leadership styles of rnilitary and civil argentines - Castro Solano, Alejandro (2004)
Based on Bass' Jeadership model (1985, 1990), the M.L.Q. questionnaire (Multifactor Leadership Questionnaire) was validated for the assessment of Jeadership styles in Argentinean civil and military population. Data were gathered (N=363) on military (cadets and officers) and ci vilian population. A factorial structure of seven grouped in three styles of Jeadership (34 items) was obtained and it was confirmed by means of confirmatory factor analysis. The results point out better adjustment of the obtained pattern for civil population than for military. Individual differences were also found among the styles of leadership of civilians and military population. In the first ones characteristics related with the exchange and the negotiation prevail. In the mi litary environments The style of transformational Jeadership prevails in military environments. In both populations valued Jeader characteristics were perceived with more intensity in self-per ception format than in the perception of subordinates regarding their superiors.